Hubungan Paparan Asap dengan Kejadian Infeksi Saluran Pernapasan Akut (ISPA) pada Anak Usia 0-5 Tahun di Wilayah Pertanian Kecamatan Panti Kabupaten Jember - Vivi Oktaviana Wulandari; Latifa Aini Susumaningrum; Tantut Susanto; Abdul Kholis (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: Acute respiratory infections (ARI) in developing countries at the age of under five have a fairly high prevalence, which relates to air pollution at home, such smoke as firewood, cigarette and mosquito coils.Methods: The purpose of this study was to examine the relationship between smoke exposure of ARI in age child 0-5 year in agricultural area Panti District, Jember Regency. A case control study design was conducted among grup control 120 and case grup 120 of respondent using stratified random sampling. A self administered questionnaire was used to interview indoor air quality. Chi Square test was perform to analyze the relationship between smoke exposure of ARI.Result: The result identified as exposure to firewood smoke 63.3%, exposure to cigarette smoke 75.8% and exposure to smoke from mosquito coils 68.3%. There were significantly relationship between firewood (χ2 = 5.813; p-value = 0.016), exposure to cigarette smoke (χ2 = 9.094; p-value = 0.004), can immediately bring mosquito coils (χ2 = 4.929; p-value = 0.037). Smoke exposure is relationship with ARI in age child 0-5 year.Conclusion : Therefore, efforts to ARI can be prevented by family who maintain air quality at home.